1984
DOI: 10.1083/jcb.99.3.1162
|View full text |Cite
|
Sign up to set email alerts
|

Tumor promoter phorbol 12-myristate 13-acetate inhibits mitogen-stimulated Na+/H+ exchange in human epidermoid carcinoma A431 cells.

Abstract: Addition of polypeptide growth factors to cultured cells results in a rapid stimulation of Na+/H ÷ exchange, which leads to cytoplasmic alkalinization. We studied the effects of the potent tumor promoter phorbol 12-myristate 13-acetate (PMA) on the Na+/H ÷ exchange system of A431 cells. Stimulation of Na+/H + exchange by epidermal growth factor (EGF) and serum as well as by vanadate ions is strongly inhibited after treatment of cells with nanomolar concentrations of PMA. Phorbol esters that have no activity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…Previous studies by Owen (14) and by Whiteley et al (27) have examined the relationship between growth factors and the phorbol ester, TPA, in activating Na/H exchange. These experiments suggested that while TPA alone stimulated Na/H exchange, when TPA was added together with epidermal growth factor it caused inhibition of epidermal growth factor-stimulated Na/H exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by Owen (14) and by Whiteley et al (27) have examined the relationship between growth factors and the phorbol ester, TPA, in activating Na/H exchange. These experiments suggested that while TPA alone stimulated Na/H exchange, when TPA was added together with epidermal growth factor it caused inhibition of epidermal growth factor-stimulated Na/H exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal calf serum may activate protein kinase C (Moolenaar et al 1981;1983) and so desensitization of receptors may occur which alters the contractile response. TPA may inhibit diacylglycerol formation by epidermal growth factor (Smith, Losonczy, Sahai, Pannerselvam, Fehnel & Salomon, 1983) and TPA may attenuate the stimulation of Na+-H+ exchange by epidermal growth factor (Whiteley, Cassel, Zhuang & Glaser, 1984). Capogrossi et at.…”
Section: K T Macleod and S E Hardingmentioning
confidence: 99%
“…Associated with this acute desensitization of EGF receptor function is an inhibition of signal transduction by the EGF receptor. EGFstimulated phosphatidylinositol turnover (12)(13)(14)(15), Na+/H' exchange (12,17), and Ca2+ fluxes (12,16) (1)(2)(3)(4)(5)(6)(7)(8)(12)(13)(14)(15)(16)(17). An hypothesis that can account for the apparent desensitization of the EGF receptor caused by PMA is that the phosphorylation of the receptor at Thr654 by protein kinase C causes an inhibition of the EGF receptor tyrosine protein kinase activity (3,4,6,10).…”
Section: Discussionmentioning
confidence: 99%
“…Phorbol ester also inhibits the increase in cytosolic Ca2+ caused by EGF without affecting basal cytosolic Ca2+ levels (12, 16). Furthermore, the EGF-stimulated Na+/H+ exchange across the plasma membrane is inhibited by phorbol ester (12,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation